2020
DOI: 10.2147/rru.s198785
|View full text |Cite
|
Sign up to set email alerts
|

<p>Management of Chronic Orchialgia: Challenges and Solutions – The Current Standard of Care</p>

Abstract: Introduction Chronic scrotal content pain (CSP) or chronic orchialgia can be debilitating for patients and difficult to treat. There is a paucity of structured treatment algorithms to approach this difficult condition. Methods A review of the literature was performed. Conservative treatment options are presented and then targeted surgical interventions that the urologist may perform are then presented in a structured algorithm format. Many of these patients may obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The management of chronic orchialgia is challenging due to the potential multifactorial causes, including ensuing psychological distress and opiate dependency. [29][30][31][32] Treatment strategies often involve a stepwise approach from the initial conservative measures and/or various neuromodulation techniques (such as pelvic floor therapy, acupuncture, pain clinic) to surgical interventions, including targeted nerve blocks, MSCD, perispermatic cord and/or ilioinguinal botox or cryoablation as well as inguinal orchiectomy. In our study, all the patients have tried various medical therapies and only 2 patients on conservative measures reported better pain control after 3 years postembolization.…”
Section: Discussionmentioning
confidence: 99%
“…The management of chronic orchialgia is challenging due to the potential multifactorial causes, including ensuing psychological distress and opiate dependency. [29][30][31][32] Treatment strategies often involve a stepwise approach from the initial conservative measures and/or various neuromodulation techniques (such as pelvic floor therapy, acupuncture, pain clinic) to surgical interventions, including targeted nerve blocks, MSCD, perispermatic cord and/or ilioinguinal botox or cryoablation as well as inguinal orchiectomy. In our study, all the patients have tried various medical therapies and only 2 patients on conservative measures reported better pain control after 3 years postembolization.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are termed neural plasticity and manifest as allodynia or hyperalgesia (Patel, 2017). Parekattil et al (2020) have observed that a significant number of patients with chronic orchialgia have Wallerian degeneration in their spermatic cords when compared to the general male population. The ligation, ablation, or neuro-modulation of the affected nerve fibers may be considered as relevant approaches for pain relief in chronic orchialgia (Parekattil et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the peripheral nerves or the spinal cord [ 54 , 55 , 56 ] and cryoablation of tissue innervation around the spermatic cord have been reported to relieve chronic scrotal pain [ 57 ].…”
Section: Neuralgiamentioning
confidence: 99%